Dominant culture and bullying : personal accounts of workers in Malaysia - Kwan, Sharon Sam Mee; Michelle R. Tuckey; Maureen F. Dollard (2014)
Workplace bullying has been termed the cancer of the workplace; it is a widespread and often intractable problem. Internationally, a wealth of research has examined the prevalence of workplace bullying and its negative effects. This research base and the scientific definition of workplace bullying are, however, based on Western perspectives and supported by theories, models, and research studies conducted in Western cultures. The differences in cultural perspectives of Western and Eastern countries mean that workplace bullying may not be understood in the same way across different cultural groups, particularly when cultures differ along the Individualism-Collectivism dimension. Given that Malaysia is an Eastern country with a number of ethnic groups, a more comprehensive understanding of workplace bullying in the Malaysian context is important. Through a case study comprising in-depth qualitative interviews with 20 employees from different organisations in Malaysia, this chapter reveals six lay beliefs of workplace bullying and 19 lay beliefs about bullying behaviors. The study also found that the 12 bullying behaviors are work related while the other seven are personal-nature bullying behaviors. These results emphasize the influence of culture on how bullying is perceived within the Malaysian context, and the importance of understanding lay representations of workplace bullying from the Eastern context that apparent across nation. Based on the interviews, a general definition of workplace bullying from Malaysian employees' perspectives is presented and developed. The chapter concludes with implications for understanding bullying as an important psychosocial hazard at work and recommendations for future research and practice across the Asia Pacific region.